Not Yet on Track to Net Zero : The Urgent Need for Greater Ambition and Policy Action to Achieve Paris Temperature Goals - Black, Simon; Parry, Ian.; Roaf, James; Zhunussova, Karlygash (Washington, D.C. : International Monetary Fund, 2021)
Achieving the Paris Agreement's temperature goals requires cutting global CO2 emissions 25 to 50 percent this decade, followed by a rapid transition to net zero emissions. The world is currently not yet on track so there is an urgent need to narrow gaps in climate mitigation ambition and policy. Current mitigation pledges for 2030 would achieve just one to two thirds of the emissions reductions needed for limiting warming to 1.5 to 2oC. And additional measures equivalent to a global carbon price exceeding USD 75 per ton by 2030 are needed. This IMF Staff Climate Note presents extensive quantitative analyses to inform dialogue on closing mitigation ambition and policy gaps. It shows purely illustrative pathways to achieve the needed global emissions reductions while respecting international equity. The Note also presents country-level analyses of the emissions, fiscal, economic, and distributional impacts of carbon pricing and the trade-offs with other instruments-comprehensive mitigation strategies will be key.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Energy; Hydrocarbon Resources; Nonrenewable Resources and Conservation; Redistributive Effects; Taxation and Subsidies